2017
DOI: 10.1111/cbdd.13035
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigations into developing all‐D Omiganan for treating Mupirocin‐resistant MRSA skin infections

Abstract: Staphylococcus aureus is the primary pathogen responsible for the majority of human skin infections, and meticillin-resistant S. aureus (MRSA) currently presents a major clinical concern. The overuse of Mupirocin, the first-line topical antibacterial drug over 30 years, has led to the emergence of Mupirocin-resistant MRSA, creating a clinical concern. The antimicrobial peptide Omiganan was touted to be a promising antibacterial drug candidate due to its rapid membrane-disrupting bactericidal mode of action, en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Interestingly, little mechanistic data has been reported to elucidate its immunomodulatory influence on host cells. In vitro, omiganan has broad spectrum antimicrobial and antifungal activity against numerous resistant species including S. aureus and Candida albicans, respectively; however, proteases endogenous to the skin can cause deactivation of the peptide in situ (Ng et al, 2017). In contrast, the D-enantiomer of omiganan is metabolically stable toward skin proteases and is comparable to the L-enantiomer in terms of antibacterial and antifungal potency.…”
Section: Synthetic Hdps and Clinical Applicationsmentioning
confidence: 99%
“…Interestingly, little mechanistic data has been reported to elucidate its immunomodulatory influence on host cells. In vitro, omiganan has broad spectrum antimicrobial and antifungal activity against numerous resistant species including S. aureus and Candida albicans, respectively; however, proteases endogenous to the skin can cause deactivation of the peptide in situ (Ng et al, 2017). In contrast, the D-enantiomer of omiganan is metabolically stable toward skin proteases and is comparable to the L-enantiomer in terms of antibacterial and antifungal potency.…”
Section: Synthetic Hdps and Clinical Applicationsmentioning
confidence: 99%
“…Our results demonstrated that naphthofuranquinones were fungicidal. An ideal biocidal agent should kill the microbes quickly to avoid the opportunity for resistance development (Ng et al, 2017). Our timekilling curve showed a rapid fungicidal effect with the use of TCH-1140 and TCH-1142.…”
Section: Discussionmentioning
confidence: 80%
“…The study of several AMPs introduced in catheter infections caused by biofilm-forming S. aureus has revealed high effectiveness of the treatment, especially in case of D-Bac8c2,5Leu [92]. Additionally, some promising data have come from the research over all-D omiganan, which has shown bactericidal activity towards S. aureus and satisfactory half-life in vivo [93].…”
Section: Novel Therapeutic Methods With the Aim Of Restoring Natural mentioning
confidence: 99%